The Effectiveness Of Using Zepeto’s Avatar On Students’ Descriptive Text Writing - Jesika Theresia Nova; Clarry Sada; Yanti Sri Rezeki (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Utilizing digital technology in English lessons, especially involving junior high school students in the process of customizing avatars from the Zepeto app, can make students more interactive and engaging, capture students' attention, and maintain engagement. This research investigated the effectiveness of using Zepeto's avatar in enhancing seventh-grade students' descriptive text writing. A quasi-experimental study was employed with a quantitative approach. Participants were 61 students from two different classes in the seventh grade, divided into an experimental group and a control group. Data was collected using a written test instrument and analyzed using t-tests and effect size data analysis. Customizing an avatar from Zepeto inspires them to write and provides them with ideas for where to start. It has been proven by the data computed, which was 5.9 as compared to 1.697 for the t-table with 30 degrees of freedom. The t-test (5,9>1,697) was shown to be greater than the t-table. The effect size formula of this experimental group was 1,02, which showed that the treatment of this study was considered a strong effect, while the control group had a moderate effect size of 0.53. The results suggest that Zepeto's avatar can be an alternative teaching media for descriptive text writing, particularly for seventh-grade students in SMP Negeri 2 Pontianak.